A Case of Inverted Papilloma Originating from the Middle Ear and Review of the Literature - Eray Bayindir; Fatih Mehmet Hanege; Mahmut Tayyar Kalcioglu; Tulay Zenginkinet; Serdal Celik (Case Reports in Otolaryngology)
Inverted papilloma (IP) with malignant transformation is rarely seen in the middle ear. Up to now, there have been 16 primary middle ear IPs reported in the English literature. Even though it is very rare in the middle ear, this pathology should be kept in mind for the differential diagnosis of middle ear masses. In this case, we report a 77-year-old female who had recurrent IP with malignant transformation and complication.